Efficacy of Short-Term Dynamic Psychotherapy in the Intervention of Marital Disturbances - Vidya Bhagat; Mainul Haque; Shivalingappa B. Javali (Journal of Global Pharma Technology, 2017)
Introduction Psychoanalysis is one of the therapeutic interventions chosen when therapies need to probe in to patients’ unconscious aspects rooted in the past. Malan’s short-term dynamic psychotherapy is a one of the types of brief psycho dynamic therapy useful in corrective emotional experiences of patients that is dynamically held with significant figures of the past. The efficacy of this therapy is studied in the current study. The selected cases of marital disharmony affected by social, emotional and sexual parameters are successfully intervened by brief psychoanalysis. The analytical probe focused on defense mechanism involved in underlying sufferings. The objective of the study is to assess the interventional successes of short-term dynamic psychotherapy in couple problems in marriage. Methods This is a case study research design that has been used to investigating of the unconscious roots of marital disturbances using short term dynamic psychotherapy. The study samples of patient couples were studied during their therapeutic intervention with consent and collected data of treatment was filed. These case reports from different institutions and field work services in India. Specifically, couple patient underwent short term dynamic psychotherapy from the 2007-2014. Interpretation of defenses was used to gain insight. The interview and free-association method was used in the study in the analysis and structuring the defense of patient. Of the 100 case studies, 40(40%) of them were intervened using short-term dynamic psychotherapy. Other cases (60%) were not indicative for short-term dynamic psychotherapy. The data was statistically analyzed by using Chi-square with Yates's correction test for association. The statistical significance was set at 5% level of significance (P<0.05). Result this result shows the fruitfulness of Short-Term Dynamic Psychotherapy in the Intervention of Marital Disturbances. More than 50% of sample population found to be highly satisfied and none patient couple was dissatisfied that shows the effective ness of this intervention.Keywords: Short-Term Dynamic Psychotherapy, Defense Analysis, Patient Couples, Marital Therapy.